2020
DOI: 10.1021/acschemneuro.0c00273
|View full text |Cite
|
Sign up to set email alerts
|

Clitoria ternatea Mediated Synthesis of Graphene Quantum Dots for the Treatment of Alzheimer’s Disease

Abstract: The main purpose of the present study was to synthesize graphene quantum dots (GQDs)from the flowers of Clitoria ternatea with the help of one-pot microwave-assisted green synthesis for the treatment of Alzheimer's disease. Further, the synthesized graphene quantum dots show a particle size of 10 nm ±1.3, a PDI of 0.354 ± 1.8, and a ζ potential of −46 ± 0.4, indicating the good stability of the quantum dots. With the help of scanning electron microscopy (SEM) and transfer electron microscopy (TEM) examination,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 36 publications
2
27
1
Order By: Relevance
“…In accordance with the previously reported ROS-and NO-scavenging activity of GQD [24,27,56,57], we used EPR, chemical radical scavenging assays, and cytofluorometry to confirm their ability to neutralize • OH, O2 •− , and NO in cell-free conditions, as well as in SNP-treated SH-SY5Y cells. Somewhat surprisingly, the cytotoxicity of SNP in our experiments was mostly independent of NO, which was only marginally involved in the protection from SNP-induced cells death.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…In accordance with the previously reported ROS-and NO-scavenging activity of GQD [24,27,56,57], we used EPR, chemical radical scavenging assays, and cytofluorometry to confirm their ability to neutralize • OH, O2 •− , and NO in cell-free conditions, as well as in SNP-treated SH-SY5Y cells. Somewhat surprisingly, the cytotoxicity of SNP in our experiments was mostly independent of NO, which was only marginally involved in the protection from SNP-induced cells death.…”
Section: Discussionmentioning
confidence: 74%
“…In conclusion, our study demonstrates that • OH/NO quenching and Akt/mTOR-dependent autophagy induction independently cooperate in GQD-mediated protection of SH-SY5Y neuronal cells from SNP-induced apoptotic death. While these findings remain to be confirmed in primary neurons and in vivo, the unique capacity of GQD to act both as antioxidants and inducers of prosurvival autophagy, coupled with low toxicity and the ability to cross blood-brain barrier [27,77] qualifies them as potential candidates for the treatment of oxidative/nitrosative stress-associated neurodegenerative and neuroinflammatory disorders.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that these carbon dots showed more percentage of inhibitions than conventional acetylcholinesterase (AChE) inhibitors due to their small size which confers them to the unique ability to cross BBB easily. These NPs prevented the aggregation of Aβ peptides [97]. In another experiment, selenium quantum dots (SeQDs) had been prepared which have high BBB activity and a high cellular uptake rate.…”
Section: Quantum Dot Nanoparticles (Qd Nps)mentioning
confidence: 99%
“…For the synthesis of quantum dots, plants have proved to be excellent precursors, thanks to their high carbon content. For this reason, the alcoholic extract of a climbing plant ( Clitoria ternatea ) was used by Tak et al [ 67 ]. The Clitoria ternatea flower extract was mixed with HPLC water and subsequently heated to 900 W in a microwave oven for 5–10 min, then the resulting residue was distributed in absolute ethanol to form a GQD dispersion.…”
Section: Gqds From Eco-friendly Raw Materials By Green Approachesmentioning
confidence: 99%